1991
DOI: 10.1128/jb.173.19.6066-6073.1991
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis, nucleotide sequence, and products of two Pseudomonas denitrificans cob genes encoding nicotinate-nucleotide: dimethylbenzimidazole phosphoribosyltransferase and cobalamin (5'-phosphate) synthase

Abstract: TnS Spr transposons have been inserted into the 8-kb Pseudomonas denitrificans DNA fragment from complementation group D, which carries cob genes. Genetic analysis and the nucleotide sequence revealed that only two cob genes (cobU and cobV) were found on this cob genomic locus. Nicotinate-nucleotide:dimethylbenzimidazole phosphoribosyltransferase (EC 2.4.2.21) was assayed and purified to homogeneity from a P.denitrificans strain in which cobU and cobV were amplified. The purified enzyme was identified as the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 32 publications
1
37
1
Order By: Relevance
“…2 (27). The sequence of these genes is homologous with that of genes of Pseudomonas denitrificans that have been shown to encode enzymes catalyzing reactions involved in joining adenosyl-CBI and DMB (2,4,5,9). These sequences and their analysis will be presented in detail elsewhere (11).…”
Section: Resultsmentioning
confidence: 99%
“…2 (27). The sequence of these genes is homologous with that of genes of Pseudomonas denitrificans that have been shown to encode enzymes catalyzing reactions involved in joining adenosyl-CBI and DMB (2,4,5,9). These sequences and their analysis will be presented in detail elsewhere (11).…”
Section: Resultsmentioning
confidence: 99%
“…Protein and oligonucleotide sequence searches made by using the BLAST algorithm (1) uncovered four new known or probable prokaryotic DAGK sequences, which are listed in Fig. 2 (6,18,22,29,36). Examination of the manually aligned sequences shows that four of the five exhibit fairly divergent sequences (e.g., <40% identity between E. coli DAGK and the DAGK from the other organisms).…”
Section: Resultsmentioning
confidence: 99%
“…7), which encodes nicotinate-nucleotide dimethyl benzimidazole phosphoribosyltransferase, participating in the cobalamin biosynthesis. 28) The sequence homology strongly suggested that the 28-kDa protein is an uroporphyrinogen III methylase. The enzymic activity was assayed and the results are presented in Table III.…”
Section: Homology To Other Sequences and Identtfication Of The 28-kdamentioning
confidence: 99%